Trade, human capital and innovation: The engines of European regional growth in the 1990s - Harald Badinger; Gabriele Tondl (European Regional Science Association (ERSA), 2002)
This paper investigates the growth factors of EU regions in the 1990s. We test the hypothesis that regional growth is determined by endogenous growth factors, trade and technological catching-up in a growth accounting framework. Our estimations suggests that growth of EU regions is positively related to the accumulation of physical and human capital. Innovation activity as well as international technology transfer are important for growth. The latter is facilitated if a region is well endowed with human capital. Further, we observe that technological catching-up is promoted by intensive foreign trade, a result which underlines the importance of trade openness for EU regions.
Keywords: 330